(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Musculoskeletal complications of diabetes have been generally ignored and poorly treated as comparedto other complications. Hence we carried out this study to find the prevalence of musculoskeletal manifestations indiabetes mellitus and its relation with age, gender and control of diabetes. Materials and methods: In the present study 100 patients of Diabetes Mellitus (DM) were studied. This was a cross sectional observational study carried out in Physical medicine and Rehabilitation Out Patient Department (OPD) of Chattagram Maa-OShishu Hospital Medical College between October 2020 to March 2021. P urposive sampling was done. Duration of diabetes, control of diabetes and any musculoskeletal complaints were noted. Correlation of musculoskeletal manifestations with age, occupation, duration of diabetes, and control of diabetes was evaluated and statistical analysis was done. After collection of all data those were analyzed by SPSS 20. Results: Among the 100 patients of DM more patients were female (72%) and most were at age group 41 to 50 years (45%). Duration of DM showed 35% patients were suffering from DM for 11- 15 years and 21% were suffering from DM for 16 -20 years. Regarding different musculoskeletal complications among DM patients adhesive capsulitis was (11%), curpal tunnel syndrome was (6%), OA knee was (10%) and planter fasciitis was (8%). Other less common complications were also found . Different complications in relation with age, gender differences and control status of DM were not significant. Conclusions: Musculoskeletal manifestations are frequent in diabetis mellitusand common complications are more among patients with higher age and findings are not related with control of diabetes. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 79-83